Everything I Know About Informatics, I Didn't Learn in Nursing School - Lynn M. Nagle (Nursing Leadership, 2007)
To date, efforts to initiate future graduates and nurses currently in practice into the world of information and communication technologies (ICTs) have been provided by relatively few nurse educators. In the past decade, nursing informatics leaders have developed a profile of informatics competencies for nurses, novice to expert - for example, the National Nursing Informatics Project (Hebert 2000) - and have demonstrated actual (Kaminski 2006) and possible informatics integration into curricula (Nagle 2001). Findings from recent studies (Nagle and Clarke 2004; Infoway 2007) suggest that a minority of Canadian schools of nursing have tackled the challenge of integrating informatics throughout their nursing curricula. When asked to respond to a recent survey (Infoway 2007), some schools decided not to participate because there were no faculty members with appropriate expertise in the area, while other schools did not regard informatics as relevant content for their program. Nevertheless, over the years, several schools of nursing have had the foresight to create a single informatics course - usually an elective - at the undergraduate or graduate level. I have held discussions with several deans and directors of schools of nursing over the past two years, and most of them recognize that this is a content area to be reckoned with sooner rather than later. No graduate nursing program has as yet created an informatics specialty option, but stay tuned.
Keywords: informatics education, nursing education, nursing curricula, electornic health record